Influence of Pressure Build-Up Time of Compression Chamber on Improving the Operation Frequency of a Single-Piston Hydraulic Free-Piston Engine - Hai-bo Xie; Hao-ling Ren; Hua-yong Yang; Jian-fei Guo (Advances in Mechanical Engineering, 2013)
A single-piston hydraulic free-piston engine with a two-cylinder four-stroke diesel engine as its driver is introduced. It takes the free-piston assembly a certain time to move after the pressure in the compression chamber starts to increase. The time difference between the pressure increasing and the piston starting to move is defined as the pressure build-up time. The characteristics of the pressure build-up time and its influence on the performance of the free-piston engine are introduced and analyzed. Based on the basic law of dynamics of the free-piston assembly, the parameters which influence the pressure build-up time are analyzed. And then improvement and optimization are proposed to shorten the pressure build-up time.